Effectiveness of selected strains of entomopathogenic nematodes in peat substrate in container breeding - Matuska-Łyżwa, Joanna (Ecological questions, 2013)
Pest control in urban green areas is particularly difficult due to the limitation of pesticide use. Using efficient methods for biological control of herbivores there may be a good solution. Planting plants growing in the forest container breeding have a better growth and better root system comparing to the seedlings produced in traditional forest nurseries. Such plants are not subject to significant shock when replanted, however, they are still exposed to pests living near plantings. Our research assessed using entomopathogenic nematodes to be introduced into the soil used for plantings in order early protect seedlings against their pests. Nematodes isolated from the natural environment as well as, for control samples, from biopreparations were used in the study. The research was conducted on the soil substrate in containers with seedlings. During the experiment were taken the following parameters: insect mortality, nematode invasion extensity, migration time of invasive larvae, number of migrating larvae, and their survival.The results showed that entomopathogenic nematodes isolated from various provinces in Poland were effective, but characterized by a diverse insecticidal activity in a peat substrate.